Evaluating Disaster Management Preparedness among Healthcare Professionals During Pandemics: Palestinian Context - Ibrahim Aqtam PhD; Mustafa Shouli PhD; Saqer Al-qoroum MsN; Khaila Shouli MsN; Ahmad Ayed PhD (SAGE Publishing, 2024)
Introduction Emergencies are increasingly prevalent, necessitating specialized management to address significant social disruption. Effective management of health emergencies requires resilience from governments and health institutions, as these emergencies are becoming more common and have wide-ranging consequences on health, society, and the economy. Due to the interconnected nature of our global society, events in one location can have international or even global impacts, as demonstrated by the COVID-19 pandemic. Objective This study aims to assess disaster management preparedness among nurses and physicians during pandemics. Methods This study used an online survey conducted in late 2022 to collect primary data through a purposive sampling method, involving both government and private hospitals in Palestine. The participants included 512 nurses and 241 physicians from various hospital units. Results The findings indicate varying levels of knowledge among participants, with a significant portion (67%) reporting no prior experience with real disaster situations. Additionally, 63% lacked prior disaster response experience. Regarding training courses, 17.8% of nurses and physicians prioritized emergency preparedness, trauma mass casualty response, and triage disaster management systems. Despite some understanding of disaster management, the study emphasizes the importance of hospital managers implementing national standards, engaging healthcare professionals in continuous education, and addressing gaps in perceived competence. Conclusion While participants demonstrated some knowledge of disaster management, the study suggests the importance of hospital managers adopting national standards, engaging healthcare professionals in continuous learning activities, and addressing perceived competence gaps.